Morphological and Physiological Mechanism of Activating Insoluble Inorganic Phosphorus of Different Peanut (Arachis hypogaea L.) Varieties under Low Phosphorus - Zhen Tan; Fengzhen Liu; Yongshan Wan; Suqing Zhu; Jing Zhang; Kun Zhang; Lu Luo (Agriculture, 2023)
To reduce the application of phosphorus fertilizer and improve phosphorus efficiency in peanut (Arachis hypogaea L.) production, six peanut varieties with different phosphorus activation efficiencies were selected, and the root morphology, physiological indexes, and types and content of organic acids secreted were measured via a hydroponic experiment for 20 days. We analyzed the difference in calcium phosphate activation between peanut seedlings cultivated under low-phosphorus (LP, 0.01 mmol/L KH2PO4) and normal phosphorus (NP, 0.6 mmol/L KH2PO4) conditions and explored the physiological mechanisms of different peanut varieties on the activation efficiency of insoluble inorganic phosphorus. The results showed that under LP conditions, the root length, root surface area, root volume, root tip number, and root activity of the efficient P activation varieties were 18.31%, 17.50%, 15.23%, 20.00%, and 50.90% higher than those of the inefficient P activation varieties respectively. The reduction range of the nutrient solution pH of the high-efficiency varieties was 74.48% higher than that of the low-efficiency varieties under LP conditions. The total amount of organic acid secreted by the efficient P activation varieties increased by 236.07% on average under LP conditions compared with that under NP conditions. In comparison, the average increase in inefficient P activation varieties was only 16.36%. Under low P stress, the peanut varieties with high-efficiency P activation could increase the activation of insoluble inorganic P in the environment mainly by changing the root architecture and increasing the root-shoot ratio, root activity, and root proton and organic acid secretion.